2011
DOI: 10.4161/mge.1.3.18300
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of the highly iterated palindrome 1 (HIP1) among prokaryotes

Abstract: Abbreviations: HIP1, highly iterated palindrome 1; HGT, horizontal gene transfer; SDR, small dispersed repeat;OpcA, glucose 6-phosphate dehydrogenase assembly proteinWe have studied the abundance and phylogenetic distribution of the Highly Iterated Palindrome 1 (HIP1) among sequenced prokaryotic genomes. We show that an overrepresentation of HIP1 is exclusive of some lineages of cyanobacteria, and that this abundance was gained only once during evolution and was subsequently lost in the lineage leading to mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…A third class was described by Robinson et al (1995) [ 3 ], HIP1 (Highly Iterated Palindrome) sites found overrepresented in many cyanobacteria [ 3 , 4 ]. The sequence, GCGATCGC, is the same in all described instances [ 4 ], although a larger sequence, GGCGATCGCC, has been recognized in two cyanobacteria [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A third class was described by Robinson et al (1995) [ 3 ], HIP1 (Highly Iterated Palindrome) sites found overrepresented in many cyanobacteria [ 3 , 4 ]. The sequence, GCGATCGC, is the same in all described instances [ 4 ], although a larger sequence, GGCGATCGCC, has been recognized in two cyanobacteria [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A third class was described by Robinson et al (1995) [ 3 ], HIP1 (Highly Iterated Palindrome) sites found overrepresented in many cyanobacteria [ 3 , 4 ]. The sequence, GCGATCGC, is the same in all described instances [ 4 ], although a larger sequence, GGCGATCGCC, has been recognized in two cyanobacteria [ 2 , 5 ]. Little is known about the biological significance of the sequence, but there is some indication that it may function in site-specific recombination in Synechococcus PCC 7002 [ 5 ] and (at a much lower efficiency) illegitimate recombination between cloned sequences in Synechococcus PCC 7942 and Escherichia coli [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIP primers used in this investigation were constructed on the basis of this frequently occurring octa palindromic sequence, which permits DNA amplification between adjacent repeated HIP sequences. The utility of HIP sequences in differentiating members of Anabaena has been reported earlier (Delaye and Moya, 2011). In a further modification of this technique, Shalini et al (2007) utilized a blend of HIP and random primer sets to create fingerprint patterns for Calothrix.…”
Section: Discussionmentioning
confidence: 98%
“…While there are no similar sequences to HIP1 in different organisms, the explanations behind this overrepresentation are obscure, although it is guessed that it might be a recombination hotspot. The HIP1 sequence can also be used to fingerprint organisms (Delaye and Moya, 2011). The HIP primers used in this investigation were constructed on the basis of this frequently occurring octa palindromic sequence, which permits DNA amplification between adjacent repeated HIP sequences.…”
Section: Discussionmentioning
confidence: 99%